RETRACTED: The role of biofield energy treatment on psychological symptoms, mental health disorders, and stress‐related quality of life in adult subjects: A randomized controlled clinical trial - Mahendra Kumar Trivedi; Alice Branton; Dahryn Trivedi; Sambhu Mondal; Snehasis Jana (Journal of General and Family Medicine)
Abstract Background Western and Eastern cultures have practiced biofield energy therapy for thousands of years, but empirical research on effectiveness of this therapy is relatively nascent. Study was aimed to assess the safety and efficacy of biofield therapy on psychological symptoms and mental health disorders in adult subjects. Methods Seventy‐seven participants (39 male and 38 female) underwent clinical trial. This trial was simple randomized, placebo‐controlled, parallel‐group, open‐label, and single‐center with subjects, who have one or more psychological symptoms. Two sessions of biofield energy attunement were given in‐person at day 0 and 90 for 3 min (treatment group, n = 35) and others allocated to naive attunement (placebo group, n = 42). Subjects were assessed psychological questionnaire scoring using standard scale of assessment and levels of physiological biomarkers in serum were determined by parameter‐specific ELISA. Results Perceived psychological symptoms/scores (asthenia, sleep disturbances, anxiety, depression, stress, confusion, future fearness, sexual desireness, motivation, confidence, emotional trauma, etc.) were significantly (p ≤ 0.0001) improved in the treatment group than placebo control group. Furthermore, physiological biomarkers: vitamins (B12, C, and D3 metabolites), immune biomarker (CD8+CD28−), neurotransmitters (acetylcholine, noradrenaline, and dopamine), hormones (oxytocin, 17‐β‐estradiol, and insulin), and antiaging protein (klotho) levels were significantly (p ≤ 0.001) increased in treatment group than placebo. Proinflammatory cytokines (TNF‐α, IL‐1β, IL‐6, and IL‐8) and oxidative stress biomarkers (isoprostane and oxidized LDL) were reduced in treatment group compared with placebo. Conclusions Results suggest that experimenter's biofield energy plays a significant role in information transfer processes that contribute to individual's state of physical, mental, emotional, and spiritual well‐being as well as improved overall health and quality of life.